Outcome Measures in Evaluation of Weighted Blankets: A Scoping Review - Maria Lönn; Ellen Odéus (Occupational Therapy International)
Conclusion: Even though there is extensive research available evaluating weighted blanket use and effects, there is a lack of standardised outcome measures and instruments are not adapted to use within occupational therapy practice. More research is necessary, informing clinical practice about which measures to use and when. Furthermore, there is a need to develop an instrument specifically tailored for use within occupational therapy practice to evaluate sleep interventions.